2023
DOI: 10.3390/metabo13020203
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Lung Cancer Diagnostics through Metabolites in Exhaled Breath: Influence of the Disease Variability and Comorbidities

Abstract: Non-invasive, simple, and fast tests for lung cancer diagnostics are one of the urgent needs for clinical practice. The work describes the results of exhaled breath analysis of 112 lung cancer patients and 120 healthy individuals using gas chromatography-mass spectrometry (GC-MS). Volatile organic compound (VOC) peak areas and their ratios were considered for data analysis. VOC profiles of patients with various histological types, tumor localization, TNM stage, and treatment status were considered. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…To address whether VOCs could distinguish lung cancer specifically, one study analyzed the VOCs in the breath using GC–MS of those with lung cancer (n = 85) and other types of cancer: esophageal (n = 11), breast (n = 22), colorectal (n = 16), kidney (n = 14), stomach (n = 7), prostate (n = 6), cervix (n = 5), and skin (n = 4) (Gashimova et al, 2023 ). The VOCs hexane, acetonitrile, 1-methyltiopropene, 1-methylthiopropane, and dimethyl sulfide were associated with lung cancer vs other cancer types, which have been associated with lung cancer previously (Rudnicka et al, 2014 ; Sakumura et al, 2017 ; Temerdashev et al, 2023 ). Breath VOCs were able to distinguish lung cancer and patients with other cancers with moderate sensitivity (68%) and specificity (69%).…”
Section: Respiratory Diseasementioning
confidence: 86%
“…To address whether VOCs could distinguish lung cancer specifically, one study analyzed the VOCs in the breath using GC–MS of those with lung cancer (n = 85) and other types of cancer: esophageal (n = 11), breast (n = 22), colorectal (n = 16), kidney (n = 14), stomach (n = 7), prostate (n = 6), cervix (n = 5), and skin (n = 4) (Gashimova et al, 2023 ). The VOCs hexane, acetonitrile, 1-methyltiopropene, 1-methylthiopropane, and dimethyl sulfide were associated with lung cancer vs other cancer types, which have been associated with lung cancer previously (Rudnicka et al, 2014 ; Sakumura et al, 2017 ; Temerdashev et al, 2023 ). Breath VOCs were able to distinguish lung cancer and patients with other cancers with moderate sensitivity (68%) and specificity (69%).…”
Section: Respiratory Diseasementioning
confidence: 86%
“…This finding holds particular significance, as elderly participants often present with a higher prevalence of comorbidities compared to their younger counterparts. These comorbidities may have introduced complexity into the eNose breathprint profiles [26]. It is noteworthy that elderly patients constitute an emerging demographic among lung cancer patients, and early lung cancer detection could enhance the feasibility of surgical interventions and further improvement of performance of eNose may be warranted [27].…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al [ 30 ] found that the concentration of 2-butanone was significantly lower in patients with stage I LC than in patients with stage II to IV LC. Conversely, Azamat et al [ 14 ] postulated an increased concentration of 2-butanone in all advanced LC stages. Azamat also found that peaks such as 2,3-Butandione and 1-methylthiopropene were significantly correlated with TNM staging of LC.…”
Section: Discussionmentioning
confidence: 99%